A review of the molecular mechanisms of hyperglycemia‐induced free radical generation leading to oxidative stress. Issue 2 (26th August 2018) - Yaribeygi, Habib; Atkin, Stephen L.; Sahebkar, Amirhossein
Abstract: The prevalence of diabetes is growing worldwide with an increasing morbidity and mortality associated with the development of diabetes complications. Free radical production is a normal biological process that is strictly controlled and has been shown to be important in normal cellular homeostasis, and in the bodies response to pathogens. However, there are several mechanisms leading to excessive free radical production that overcome the normal protective quenching mechanisms. Studies have shown that many of the diabetes complications result from excessive free radical generation and oxidative stress, and it has been shown that chronic hyperglycemia is a potent inducer for free radical production, generated through several pathways and triggering multiple molecular mechanisms. An understanding of these processes may help us to improving our preventive or therapeutic strategies. In this review, the major molecular pathways involved in free radical generation induced by hyperglycemia are described. Abstract : Studies have shown that many of the diabetes complications result from excessive free radical generation and oxidative stress, and it has been shown that chronic hyperglycemia is a potent inducer for free radical production, generated through several pathways and triggering multiple molecular mechanisms. An understanding of these processes may help us to improving our preventive or therapeutic strategies. In this review, the major molecular pathways involved in free radical generation induced by hyperglycemia are described.